Behavioural cardiovascular risk factors and prevalence of diabetes in subjects with familial hypercholesterolaemia. (October 2020) - Perez-Calahorra, Sofia; Civeira, Fernando; Guallar-Castillón, Pilar; Pinto, Xavier; Banegas, José R; Pedro-Botet, Juan; Suarez-Tembra, Manuel; Mauri, Marta; Soler, Cristina; Rodriguez-Artalejo, Fernando; Laclaustra, Martín
A low prevalence of type 2 diabetes mellitus has been reported in familial hypercholesterolaemia. Whether a healthier lifestyle could explain it has not been explored. This cross-sectional study determines the prevalence of lifestyle-related cardiovascular risk factors in heterozygous familial hypercholesterolaemia (HeFH) from the Dyslipidaemia Registry of the Spanish Atherosclerosis Society and in the ENRICA study, a representative sample of the adult Spanish general population, weighted to match the age and sex distribution of the HeFH sample. A total of 2185 HeFH patients and 11, 856 individuals from ENRICA were included. HeFH had lower body mass index and fewer of them were smokers than in the reference population. A model adjusted for age, sex and body mass index showed that HeFH more frequently had cardiovascular disease (odds ratio (OR) 23.98; 95% confidence interval (CI) 18.40–31.23) and hypertension (OR 1.20; 95% CI 1.07–1.35), and took anti-hypertensive medication (OR 1.36; 95% CI 1.18–1.56) and anti-diabetic medication (OR 1.25; 95% CI 1.00–1.56), but less frequently were smokers (OR 0.79; 95% CI 0.71–0.89). In a HeFH subsample ( n  = 513) with complete blood glucose information, those patients without cardiovascular disease showed lower prevalence of smoking and type 2 diabetes mellitus, lower body mass index and glucose, and higher diastolic blood pressure than the Spanish population. The differences in type 2 diabetes mellitus were justified mostly by the difference in body mass index. Body mass index adjustment also showed higher prevalence of hypertension and use of anti-hypertensive drugs in HeFH. In summary, HeFH patients had lower body mass index, which may contribute to explaining the lower prevalence of diabetes, and lower current smoking but higher hypertension.